Inovasi Pragmatis dalam Penerapan Kurikulum Pendidikan Modern Pada Kurikulum Merdeka - Nurjanah, Nurjanah; Abdussalam, Agus; Anwar Muhtadin, Dedi; Suryana, Suryana (Muttaqien Publsihing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2025)
The rapid development of the times requires the world of education to adapt by implementing a flexible and relevant curriculum. This article analyzes pragmatic innovations in implementing the Merdeka Curriculum to improve the quality of education. The research method used is a qualitative approach with a literature study, where data is collected through analyzing literature related to curriculum and teaching. The results show that the Merdeka Curriculum emphasizes the development of 21st-century competencies and differentiated learning, which allows learners to learn according to their needs and abilities. The discussion reveals that the success of curriculum implementation depends heavily on the role of the teacher as a facilitator and motivator, as well as the importance of school management support in creating an effective learning environment. The findings provide important insights for curriculum development in Indonesia to achieve better educational goals.